Cretaceous deposits in the Precordillera of La Rioja (Ciénaga del Río Huaco Formation) - Ciccioli, P.L. (2005)
This paper reports the presence of Maastrichtian rocks in the north of the Precordillera (La Rioja province). The Cretaceous succesion (122 m thick) is a classical red bed sequence composed of sandstones, mudstones, marls and thin levels of evaporites. According to lithological features 6 facies associations have been recognized that mainly characterize a lacustrine system developed under arid to semiarid conditions. Probably as a result of an increase in aridity, eolian sediments were deposited at the top of the Cretaceous unit. At least two transgressive-regressive events have been recognized in the lacustrine sequence. The best developed is the first event formed by fossiliferous black shales corresponding to the maximum flooding stage. These rocks have yield remains of calcareous microfossils, palynomorphs and gastropods. The former comprise charophytes, with Platychara compressa (Knowlton) an Tectochara sp. A Musacchio, anda ostracods, with Ilyocypris wichmanni punctata Musacchio y Simeoni, Eucandona? sp., Cypridopsis and Ovo cytheridea? rionegrensis Musacchio.. Palinomorphs form a monospecific assemblage of algae colonies corresponding to Pediastrum. The lithological features, stratigraphic location and fossiliferous remains clearly suggest a regional correlation with the Ciénaga del Rio Huaco Formation. This correlation considerably enlarge the regional distribution of the Cretaceous sediments which were previously limited to the Precordillera of San Juan province. © 2005 Asociación Geológica Argentina.